Geographies of science - Meusburger, Peter (Knowledge and space, 2010)
These essays explore the understanding of historical and contemporary geographies of science. From the 16th to the 20th centuries, they examine the formation and changing geographies of such scientific centers as museums, laboratories and world fairs.